Pengaruh Panjang Serat Dan Fraksi Volume Serat Pelepah Kelapa Terhadap Ketangguhan Impact Komposit Polyester - Sari, Nasmi Herlina; Zainuri, Achmad; Wahyu, Fitratul (Universitas Mataram, 2011)
Composite has alone top to be compared with alternative's tech material any other as strong, demulcent, bate corrosion, economic etcetera. The aim of this research is to investigate the influence of fiber length and fiber volume composition coconut frond to tensile strength step-up and toughness impact composite is coconut frond fiber with matrix resin polyester This research utilizes fiber length variation 2 cm, 4 cm, 6 cm and fiber volume variations 5%, 10%, 15%. composite lasing utilizes resin polyester composite makings done at random with fiber compare and resin 100%. Fiber conduct is done with soak fiber up to 1 hour with NaOH solution as much 4%. composite makings process by method hand lay up with emphasis manually utilize glass as printed as and depressing. That result showed for fiber length 2 cm, 4 cm, and 6 cm gotten by supreme tensile strengths on long fiber 6 cm which is 27.5503216 N/mm2 and tensile strength is contemned available on fiber length 2 cm which is 16.80040936 N/mm2 and on fiber volume 5%,10%, and 15% supreme tensile strengths on volume fiber 15%, which is 28.49020468 N/mm2 and tensile strength is contemned available on volume 5%, which is 16.80040936 N/mm2. Toughness impact supreme for fiber length 2 cm, 4 cm, and 6 cm happens on fiber length 2 cm with volume variation 10% which is 4087.5 Kj/m2 and on fiber volume 5%,10%, and 15% gotten by toughness impact supreme available on volume 10% with longing fiber 6 cm which is, 4087. 5 Kj/m2